(untitled) (Archives of Clinical Psychiatry, 2012)
BACKGROUND: The occurrence of a pre- or postnatal diagnosis of a congenital anomaly may imply changes in the family dynamics and functioning, and may have an important impact on the parents' individual adjustment. OBJECTIVES: This study aimed to assess the perceived burden and individual adjustment of parents whose child has a congenital anomaly, and to examine the variability of parental adaptation (burden and individual adjustment) as a function of the child's characteristics. METHODS: The sample comprised 124 parents (62 couples), whose child has a congenital anomaly. The assessment protocol included the Impact on Family Scale, the Brief Symptom Inventory, and the World Health Organization quality of life instrument (WHOQOL-Bref). RESULTS: Mothers reported higher scores on psychopathological symptoms and lower scores on quality of life than fathers. A significant effect of child's age in the paternal adaptation was found; the perception of the severity of the anomaly was significantly associated with paternal adjustment and with maternal burden. In both parents, the timing of diagnosis and the type of congenital anomaly were significantly correlated with global and financial burden. DISCUSSION: These findings support the complexity of the parents' adaptation when parenting a child with a congenital anomaly, in which several factors interact, particularly those associated with the child's diagnosis.